2016
DOI: 10.1080/01904167.2016.1143500
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest calcium applications improve postharvest quality of papaya fruits (Carica papayaL. cv. Eksotika II)

Abstract: This research was conducted to evaluate the effects of calcium chloride (CaCl2) and calcium nitrate Ca(NO3)2 on nutrient concentrations and post-harvest quality of papaya fruits. In the first experiment, plant stem height increased significantly after Ca(NO3)2 application compared to CaCl2. Calcium content in peel and pulp for both sources significantly rose with increasing calcium concentrations, but there was a significantly higher content of calcium in fruit peel and pulp in the CaCl2 treatment. Magnesium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
0
10
1
1
Order By: Relevance
“…Previous studies directly link an increase in yields with calcium application [7]. Calcium chloride and calcium nitrate compounds have been reported to be applied in various fruits including papaya [8] and guavas. These salts are applied at varied rates and timing, mostly after physiological maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies directly link an increase in yields with calcium application [7]. Calcium chloride and calcium nitrate compounds have been reported to be applied in various fruits including papaya [8] and guavas. These salts are applied at varied rates and timing, mostly after physiological maturity.…”
Section: Introductionmentioning
confidence: 99%
“…This statement was supported by the study of Maftoonazad and Ramaswamy [ 51 ], who revealed that the atmosphere composition around the fruit has a significant role in AA retention during storage. Magwaza et al [ 47 ] and Madani et al [ 52 ] added that lower C 2 H 4 production in fruits improved AA retention, which was confirmed when C 2 H 4 production was measured and revealed a low concentration in KH Nps-coated papaya.…”
Section: Resultsmentioning
confidence: 88%
“…However, in tomatoes (Solanum lycopersicum), papayas (Carica papaya) and lemon (Citrus limon), these produces are less susceptible to chilling injury (Wang, 1994). Calcium is one of the chemical treatments used apparently to strengthen the cell walls and cell membranes in order to withstand the chilling stress in okra (Abelmoschus esculentus), papaya (Carica papaya), peach (Prunus persica) and tomatoes (Solanum lycopersicum) (Madani et al, 2016;Sohail et al, 2015). Growth regulator, such as abscisic acid (ABA) is used to alter the chilling tolerance of tissues by inducing stomatal closure, reduce water loss, and prevent chilling-induced wilting of seedlings (Tijero et al, 2016).…”
Section: Postharvest Technique In Reducing Chilling Injurymentioning
confidence: 99%